2018
DOI: 10.1002/jcb.27559
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effects of microRNA‐494 on proliferation, migration, invasion, and apoptosis of medulloblastoma cells by mediating c‐myc through the p38 MAPK signaling pathway

Abstract: Medulloblastoma (MB) is the most prevalent brain tumor that occurs during childhood and originates from cerebellar granule cell precursors. Based on recent studies, the differential expression of several microRNAs is involved in MB, while the role of microRNA‐494 (miR‐494) in MB remains unclear. Therefore, we conducted this study to investigate the regulative role of miR‐494 in MB cells via the p38 mitogen‐activated protein kinase (MAPK) signaling pathway by mediating c‐myc. In the current study, MB cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Luckily, through preliminary data mining, we discovered that Myc has a close relationship with MAPK signaling pathway. More importantly, several studies uncovered that Myc expression was positively related to MAPK signaling pathway in asthma airway remodeling [34], osteoarthritis [35], and some tumors [36,37]. In steps with the previous, we discovered that depletion of Myc in LPS model can block the expression of p-P38 MAPK and p-JNK.…”
Section: Discussionsupporting
confidence: 72%
“…Luckily, through preliminary data mining, we discovered that Myc has a close relationship with MAPK signaling pathway. More importantly, several studies uncovered that Myc expression was positively related to MAPK signaling pathway in asthma airway remodeling [34], osteoarthritis [35], and some tumors [36,37]. In steps with the previous, we discovered that depletion of Myc in LPS model can block the expression of p-P38 MAPK and p-JNK.…”
Section: Discussionsupporting
confidence: 72%
“…Among the significant findings that summarized in our study, one of them suggested that miR-494 was down-regulated in hippocampal tissues of rats with Ep. Similar to this finding, the degradation of miR-494 has been verified in medulloblastoma tissues [11]. Cheng et al have found that the expression of miR-494 was repressed in cervical cancer [27].…”
Section: Discussionsupporting
confidence: 66%
“…miR-494 is situated at chromosome 14q32.31 [8] and has been revealed to be downregulated in temporal cortex of patients with mesial temporal lobe epilepsy (mTLE) [9]. Its mechanism functions have also been demonstrated in other neurological diseases, such as glioblastoma [10] and medulloblastoma [11]. Moreover, receptor-interacting protein kinase 1 (RIPK1) is a member of a serine-threonine kinase family that transfers inflammatory and cell death signals after death receptor ligation, activation of pattern recognition receptors, as well as DNA injury [12].…”
Section: Introductionmentioning
confidence: 99%
“…BDNF participates in the classical MAP kinase pathway by binding to its tyrosine kinase receptor TrkB, leading to cell proliferation and differentiation [ 21 ]. Downregulated c-myc could inactivate the p38 MAPK pathway and suppress cell proliferation and migration [ 22 ], suggesting that the upregulated c-myc observed in our study may induce these responses. DUSP is a group of dual-specificity phosphatases that are closely related to MAPK and mostly negatively regulate their function.…”
Section: Discussionmentioning
confidence: 97%